PENGEMBANGAN SISTEM INFORMASI TERPADU PAUD STUDI KASUS PAUD ASI (AURA SUKMA INSANI) SINGARAJA - ., Kadek Dwinda Yudha Pratama; ., I Made Agus Wirawan, S.Kom., M.Cs.; ., I Gede Mahendra Darmawiguna, S.Kom., M.S (Universitas Pendidikan Ganesha, 2019)
Pendidikan merupakan usaha sadar yang dilakukan untuk meningkatkan kualitas masyarakat. Pemerintah melalui pendidikan pada usia dini memiliki visi untuk meningkatkan kualitas masyarakat. Meningkatkan kualitas pendidikan sudah menjadi faktor penentu untuk menunjang meningkatnya kualitas masyarakat, semakin baik pendidikan yang diberikan maka semakin baik keluaran yang dihasilkan. Upaya untuk meningkatkan kualiats pendidikan salah satunya dengan mengembangkan pengelolaan dalam lembaga pendidikan, pengelolaan yang dimaksud adalah pengelolaan administrasi. Pengembangan pengelolaan ini dilakukan dengan mengembangkan sistem informasi terpadu. Metode penelitian yang digunakan adalah penelitian pengembangan dengan model waterfall. Sistem informasi dikembangkan dengan framework Laravel dan Android Studio. Sistem dapat berjalan online maupun offline sesuai dengan kebutuhan dari lembaga pendidikan.. Hasil penelitian ini berupa sistem informasi terpadu yang dapat diakses dengan komputer pada server dan smartphone android pada client. Berdasarkan hasil pengujian, sistem informasi bekerja dengan baik. Sistem dinilai mampu untuk membantu masalah adminisrasi dengan presentasi nilai yaiitu 84,67 %. Sistem mendapat respon yang positif dari pengguna.Kata Kunci : Sistem Informasi, Android, Client Server, Pendidikan, Akademik Education is a conscious effort carried out to improve the quality of society. The government through education at an early age has a vision to improve the quality of society. Improving the quality of education has become a determining factor to support the increasing quality of society, the better the education provided, the better the output produced. One of the efforts to improve the quality of education is by developing management in educational institutions, management in question is administrative management. Management development is carried out by developing integrated information systems. The research method used is development research with the waterfall model. Information systems are developed with the Laravel and Android Studio framework. The system can run online or offline according to the needs of educational institutions. The results of this study are integrated information systems that can be accessed by computers on the server and android smartphone on the client. Based on the results of testing, the information system works well. The system is considered capable of helping administration problems with presentation values which are 84.67%. The system received a positive response from usersEducation is a conscious effort carried out to improve the quality of society. The government through education at an early age has a vision to improve the quality of society. Improving the quality of education has become a determining factor to support the increasing quality of society, the better the education provided, the better the output produced. One of the efforts to improve the quality of education is by developing management in educational institutions, management in question is administrative management. Management development is carried out by developing integrated information systems. The research method used is development research with the waterfall model. Information systems are developed with the Laravel and Android Studio framework. The system can run online or offline according to the needs of educational institutions. The results of this study are integrated information systems that can be accessed by computers on the server and android smartphone on the client. Based on the results of testing, the information system works well. The system is considered capable of helping administration problems with presentation values which are 84.67%. The system received a positive response from userskeyword : Information System, Android, Client Server, Education, Academic